Hot melt electrode layer-forming organopolysiloxane composition, laminate provided with electrode layer, use therefor, and method for producing same
By developing a hot melt electrode layer formative organopolysiloxane composition, the problem that the electrode formative composition in the prior art is not suitable for solvent-free processes and interface peeling is solved, and a high-performance electrode layer is formed in a solvent-free process.
Patent Information
- Application Number
- CN202380067502.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-29
- Filing Date
- 2023-09-26
- Publication Date
- 2025-04-29
AI Technical Summary
The existing electrode-forming compositions are suitable for liquid or solvent coating processes, and cannot be applied to solvent-free processes. In transducers with large physical displacement, the interface peeling between the dielectric layer and the electrode layer is prone to occur, affecting performance.
A hot melt electrode layer formative organopolysiloxane composition is developed, which comprises chain-shaped organopolysiloxane, organopolysiloxane resin and conductive fine particles, which can be non-fluidic at 25°C and has heating and melting properties, and is suitable for solvent-free processes.
The electrode layer with uniform and practical and sufficient viscoelastic characteristics is achieved in the solvent-free process, which improves the heat resistance, durability, adhesion and follow-up of the dielectric layer, and reduces the peeling and defects of the electrode layer.
Smart Images

Figure BDA0005320517390000201 
Figure BDA0005320517390000202 
Figure BDA0005320517390000211
Abstract
Description
Technical Field
[0001] The present invention relates to a hot-melt electrode layer-forming organopolysiloxane composition, which is non-fluid to solid at 25° C. and has fluidity upon heating, a laminate having an electrode layer formed using the composition, uses thereof, a production method thereof, and a production apparatus thereof. Background Art
[0002] Cured organopolysiloxanes having a polysiloxane skeleton have excellent transparency, electrical insulation, heat resistance, cold resistance, etc., can improve electrical activity by introducing high dielectric functional groups such as fluoroalkyl groups as desired, and can be easily processed into films or sheets, and are therefore used in various applications, represented by adhesive films for various electrical / electronic equipment or electroactive films for transducer devices such as actuators. These cured organopolysiloxanes are classified into hydrosilylation reaction curing type, condensation reaction curing type, peroxide curing type, etc. according to their curing mechanism. In particular, since they are rapidly cured by being left at room temperature or heated, and do not generate by-products, cured organopolysiloxane films using curable organopolysiloxane compositions of the hydrosilylation reaction curing type are commonly used.
[0003] On the other hand, when using an organopolysiloxane cured film as an electronic material for a touch panel or the like, an electronic component for a display device, and particularly a transducer material such as a sensor or an actuator, it is necessary to provide an electrode layer on the electroactive film as a dielectric layer. For example, non-patent documents 1 and 2 propose that an electrode layer having excellent followability to a dielectric layer be formed by adding a conductive filler to an organosilicone elastomer matrix having excellent flexibility.
[0004] However, when an electrode layer to which a conductive filler is added is to be formed on an organopolysiloxane cured film as an electroactive film, in particular, as the dielectric layer is displaced (e.g., expansion and contraction of an actuator, etc.), the interface between the dielectric layer and the electrode layer is peeled off, which sometimes leads to poor conduction and reduced reliability as an actuator. The applicant of this case and others proposed in Patent Document 1, etc. that a curable organopolysiloxane composition containing a conductive filler is applied on an organopolysiloxane cured film as an electroactive film, thereby forming an electrode layer as an organopolysiloxane cured film on the electroactive film (= dielectric layer), and proposed that as a transducer material for an actuator, in order to improve the followability of the electrode surface, a laminate of functional groups that participate in a common curing reaction to form chemical bonds at the interface is used in the dielectric layer / electrode layer forming organopolysiloxane composition (Patent Document 2).
[0005] Prior art literature
[0006] Non-patent literature
[0007] Non-patent literature 1: Kujawski, M.; Pearse, JD; Smela, E. Carbon 2010, 48, 2409-2417.
[0008] Non-patent document 2: Rosset, S.; Shea, HR Appl. Phys. A 2013, 110, 281-307.
[0009] Patent Literature
[0010] Patent Document 1: International Patent Publication No. WO2014 / 105959
[0011] Patent Document 2: International Patent Publication No. WO2022 / 004462 Summary of the invention
[0012] Problems to be solved by the invention
[0013] However, the inventors have found potential problems in these processes. That is, the known electrode-forming compositions are all suitable for coating processes using liquid or solvents, and cannot be applied to solvent-free processes and electrode printing processes in recent years for the purpose of reducing environmental load and improving the performance of actuators, etc., and the applicable processes are limited, so there are potential problems in their industrial development. Further, since these electrode-forming compositions are liquid compositions, in terms of their transportation, utilization and storage stability, by providing a composition with better handling properties, it is expected to further promote industrial utilization.
[0014] On the other hand, conventional electrode-forming compositions are applied by a coating process using a liquid or solvent, thereby ensuring to some extent the uniformity of the formed electrode, practically acceptable followability of the substrate, etc. However, when a solvent-free or non-fluid form is used as the electrode-forming composition, even if an electrode layer is arranged on a dielectric layer, it will become uneven during coating, or the obtained electrode layer will not be able to achieve sufficient viscoelasticity, and especially when applied to a transducer with a large physical displacement, the shape of the electrode cannot be maintained, and there is a great concern that its performance cannot be fully exerted.
[0015] The present invention is completed to solve the above-mentioned problems, and its purpose is to provide an electrode layer forming composition, a laminate using the same, its use and a manufacturing method. The composition can be used in a substantially solvent-free process and can be applied to various processes including an electrode printing process (printing). Since the composition itself is non-fluid to solid, it has excellent handling properties and storage stability, can be applied in a heating and melting (hot melting) process, and the heat resistance, durability, adhesion to the dielectric layer, tracking properties and shape retention of the obtained electrode are significantly excellent. Even when using a transducer such as an actuator that is based on a high degree of physical displacement, it is not easy to produce problems such as peeling and defects of the electrode layer, and an electrode layer with viscoelastic properties sufficient for practical use can be formed.
[0016] Solutions for solving problems
[0017] The inventors of the present invention have conducted intensive research and found that the above-mentioned problems can be solved by a hot-melt electrode layer-forming organopolysiloxane composition, thereby completing the present invention. The composition comprises: (A) a chain organopolysiloxane; (B) an organopolysiloxane resin having a weight average molecular weight of 5000 or more in terms of standard polystyrene and containing R 3 SiO 1 / 2 (wherein R independently represents a monovalent organic group) and a siloxane unit (M unit) composed of SiO 4 / 2 The composition is non-fluid and heat-meltable at 25°C, and the content of component (B) in the composition is 45% by mass or more relative to the entire composition. In a conventional silicone composition, it is difficult to obtain an electrode layer with sufficient viscoelastic properties for practical use by only performing a hot-melt composition design, but the above-mentioned problem can be well solved by satisfying the use of the above-mentioned specific components and the range of their usage.
[0018] From the perspective of solving the problem, the hot-melt electrode layer-forming organopolysiloxane composition of the present invention is preferably substantially solvent-free and does not contain a detectable amount of solvent. Further, from the perspective of achieving viscoelasticity and excellent conductivity of the obtained electrode layer, (E) conductive particles are preferably particles containing at least one conductive carbon selected from carbon nanotubes (CNTs), conductive carbon black, graphite, and vapor-grown carbon (VGCF), and it is particularly preferred to use a certain amount of fibrous conductive carbon such as single-walled carbon nanotubes (SWCNTs).
[0019] In addition, the above-mentioned problem is solved by a laminate having a structure in which an electrode layer (L2) composed of the above-mentioned hot-melt electrode layer-forming organic polysiloxane composition is stacked on at least one side of an organic polysiloxane cured film (L1) as a dielectric layer, and its use (including a transducer component, a transducer, an electronic component or a display device).
[0020] Furthermore, the above-mentioned problem is solved by the following method for manufacturing a laminate and a method for forming an electrode layer in a transducer component comprising the manufacturing method, the manufacturing method comprising: step I: a step of curing a curable organopolysiloxane composition that provides a dielectric layer by curing into a film state, thereby obtaining an organopolysiloxane cured product film as a dielectric layer; step II: a step of heating and melting the above-mentioned hot-melt electrode layer-forming organopolysiloxane composition on the organopolysiloxane cured product film involved in step I or on its precursor, thereby forming an electrode layer.
[0021] Effects of the Invention
[0022] According to the present invention, it is possible to provide an electrode layer forming composition, a laminate using the same, and its use and manufacturing method. The electrode layer forming composition can be used in a substantially solvent-free process and can be applied to a variety of processes including printing. Since the composition itself is non-fluid to solid, it is excellent in handling and storage stability, and the obtained electrode is significantly excellent in heat resistance, durability, adhesion to the dielectric layer, tracking and shape retention. Even when using a transducer that is based on a high degree of physical displacement such as an actuator, it is not easy to cause the problem of peeling and defects of the electrode layer, and it is possible to form an electrode layer with viscoelastic properties sufficient for practical use. In particular, according to the present invention, it is possible to provide a flexible process design including a solvent-free process, and it is not easy to cause interface peeling with an organic polysiloxane cured film as a dielectric layer, poor current conduction, and excellent reliability in the use of actuators, etc. The laminate and its manufacturing method can be provided. DETAILED DESCRIPTION
[0023] [Hot-melt electrode layer-forming organopolysiloxane composition]
[0024] First, the hot-melt electrode layer-forming organopolysiloxane composition of the present invention (hereinafter referred to as "the present composition") is described. The present composition is characterized in that it comprises: (A) a chain organopolysiloxane; (B) an organopolysiloxane resin having a weight average molecular weight of 5000 or more in terms of standard polystyrene and containing R 3 SiO 1 / 2 (wherein R independently represents a monovalent organic group) and a siloxane unit (M unit) composed of SiO4 / 2 The composition is non-fluid and heat-meltable at 25° C., and the content of the component (B) in the composition is 45% by mass or more relative to the entire composition.
[0025] Among them, "having heat-melting properties" means that the softening point is above 50°C, has a melt viscosity at 150°C (preferably a melt viscosity of less than 1000 Pa·s), and has the property of flowing. On the other hand, when the softening point is above 200°C, it is above the normal use temperature for molding purposes, so it is defined as "not having heat-melting properties". It should be noted that, in this article, heat-melting properties are sometimes referred to as "hot melt properties". In addition, since the present composition has heat-melting properties, it is specified as a "hot melt type" composition.
[0026] The present composition is non-flowable at 25°C. Here, non-flowable means that it does not deform / flow under no load. Preferably, when formed into granules or tablets, it does not deform / flow under 25°C and no load. Such non-flowability can be evaluated, for example, by placing the formed present composition on a hot plate at 25°C, and it does not substantially deform / flow under no load or even when a certain load is applied. The reason is that if it is non-flowable at 25°C, the shape retention at this temperature is good and the surface adhesiveness is low.
[0027] The softening point of the present composition is preferably 100° C. or lower. The softening point is a temperature at which the deformation in the height direction becomes 1 mm or more when a 100-g load is continuously pressed from above on a hot plate for 10 seconds and the deformation of the composition is measured after the load is removed.
[0028] From the viewpoint of the viscoelasticity of the electrode layer obtained by using the present composition and the uniform coating property based on the heat melting property, the shear storage modulus (G') of the composition at 110°C before electrode formation (especially before the curing reaction) is 110℃ ) and shear storage modulus (G') at 25 °C 25℃ ) value ratio (G' 110℃ / G' 25℃ ) is preferably 0.5 or less, more preferably in the range of 0.01 to 0.50, and particularly preferably in the range of 0.02 to 0.45. It should be noted that (G') of the composition after electrode formation (especially after curing reaction) 110℃ / G' 25℃ ) is also preferably less than 0.5, and may be in the range of 0.05 to 0.45, and is preferred. On the other hand, if the composition (G') before or after electrode formation (particularly after curing) is 110℃ / G' 25℃ ) value exceeds 0.5, which means that the temperature dependence of the viscoelasticity of the electrode layer is small, and sometimes there will be performance problems such as being unable to achieve the improvement of processability by heating and maintaining the shape of the electrode layer.
[0029] The viscoelasticity of the electrode layer obtained using the present composition is not particularly limited, but after the electrode layer is formed, the shear storage modulus (G' 25℃ ) can be 1.0×10 5 ~7.5×10 6 The range of Pa, in addition to the above-mentioned temperature dependence, can also achieve practically sufficient viscoelasticity of the electrode layer. In addition, from the perspective of the viscoelasticity of the electrode layer obtained using the present composition, the value of tanδ of the composition at 25°C before or after electrode formation (especially after curing) is particularly preferably 0.30 or more, and in particular, the value of tanδ of the composition before electrode formation is preferably in the range of 0.35 to 0.99. This is because, when the viscoelasticity of the present composition or the electrode layer composed of it satisfies the above-mentioned conditions, it is not easy to cause the problem of peeling and defects of the electrode layer, and an electrode layer with practically sufficient viscoelastic properties can be formed.
[0030] Here, in order to make the present composition have heat-melting properties and to exert the excellent viscoelasticity in the electrode layer as described above, the present composition at least comprises: (A) a chain organopolysiloxane; (B) an organopolysiloxane resin having a weight average molecular weight of 5000 or more in terms of standard polystyrene and containing R 3 SiO 1 / 2 (wherein R independently represents a monovalent organic group) and a siloxane unit (M unit) composed of SiO 4 / 2 The composition comprises a siloxane unit (Q unit) as shown; and (E) conductive particles, and the content of component (B) in the composition needs to be 45% by mass or more relative to the entire composition. It should be noted that the composition may be a curing reactive composition, or may be heated and melted to form an electrode layer as a curing reactant, or may be heated and melted to form an electrode layer as a non-flowing solid layer (including so-called dry-up), without any particular limitation.
[0031] [Ingredients (A)]
[0032] Component (A) is a chain organopolysiloxane, which is used together with a certain amount of component (B) to achieve heating meltability as a whole composition, and is a component that achieves good temperature dependence of viscoelasticity in the obtained electrode layer. Such a chain organopolysiloxane can be exemplified by a substance having a straight chain or a branched structure with a few branch points, but a straight chain organopolysiloxane is particularly preferred in practice. In the case of using a highly branched organopolysiloxane, heating meltability may not be achieved, or the electrode layer may be hardened and viscoelasticity may not be obtained, which is not preferred.
[0033] Component (A) may not have a curing reactive functional group, but regardless of whether the composition as a whole has curing reactivity, (A1) is preferably a linear organopolysiloxane having a curing reactive functional group containing a carbon-carbon double bond at least at both ends of the molecular chain. The curing reactive functional group containing a carbon-carbon double bond is a curing reactive group selected from alkenyl groups having 2 to 20 carbon atoms such as vinyl groups; and groups containing (meth)acryloyl groups such as 3-acryloxypropyl groups and 3-methacryloxypropyl groups, and alkenyl groups having 2 to 6 carbon atoms are particularly preferred.
[0034] The chain organopolysiloxane in component (A) may contain a group selected from a monovalent hydrocarbon group having no carbon-carbon double bond in the molecule, a hydroxyl group, and an alkoxy group having 1 to 3 carbon atoms. In addition, in the monovalent hydrocarbon group, part of the hydrogen atoms may be substituted by a halogen atom or a hydroxyl group. Industrially, methyl, phenyl, hydroxyl, and alkoxy groups are preferred.
[0035] Preferably, component (A1) has at both ends of its molecular chain
[0036] (Alk)R 2 2 SiO 1 / 2
[0037] (wherein Alk is an alkenyl group having 2 or more carbon atoms), and the other siloxane units are substantially composed only of R 2 2 SiO 2 / 2 A linear organopolysiloxane composed of the siloxane units shown in the formula: 2 The siloxane polymerization degree of component (A1) is within the range of 7 to 1002, including the terminal siloxane unit, and may be within the range of 102 to 902.
[0038] [Ingredient (B)]
[0039] Component (B) is one of the characteristic components of the present invention, and provides hot melt properties as a whole composition, and by using it together with the above-mentioned component (A) within a certain amount range, the present composition is provided with sufficient hot melt properties in practical use, and the obtained electrode has excellent heat resistance, durability, adhesion to the dielectric layer, followability and shape retention. Specifically, component (B) is an organopolysiloxane resin, which uses an organic solvent such as toluene and xylene, and has a weight average molecular weight of 5000 or more in terms of standard polystyrene measured by GPC (gel permeation chromatography), and has an M unit and a Q unit in the molecule.
[0040] The first characteristic of component (B) is that it is a high molecular weight organopolysiloxane resin having a weight average molecular weight of 5000 or more. From the viewpoint of heat-melting property and shape retention of the obtained electrode, the weight average molecular weight of component (B) is preferably 5500 or more, 6000 or more, and industrially particularly preferably in the range of 5500 to 100,000, 6000 to 50,000. On the other hand, if the weight average molecular weight of component (B) is less than the above lower limit (i.e., low molecular weight organopolysiloxane resin), even if a certain amount or more of component (B) containing M / Q units is formulated, it is sometimes impossible to achieve sufficient temperature dependence of viscoelasticity, heat-melting property and shape retention of the electrode as a whole composition.
[0041] The component (B) has a 3 SiO 1 / 2 (wherein R independently represents a monovalent organic group) and a siloxane unit (M unit) composed of SiO 4 / 2 The siloxane unit (Q unit) shown may also optionally contain a siloxane selected from R 2 SiO 2 / 2 (D unit) and RSiO 3 / 2 The siloxane unit in (T unit), the component (B) is composed of the following average unit formula:
[0042] (R 3 SiO 1 / 2 )p(R 2 SiO 2 / 2 )q(RSiO 3 / 2 )r(SiO 4 / 2 )s(XO 1 / 2 )t
[0043] The organopolysiloxane resin shown.
[0044] R is a monovalent organic group, and may be a curing reactive group containing a carbon-carbon double bond, or may be a group selected from a monovalent hydrocarbon group, a hydroxyl group, and an alkoxy group that does not have a carbon-carbon double bond in the molecule.
[0045] Specifically, the curing reactive group containing a carbon-carbon double bond as R can be exemplified by a curing reactive group selected from the following: alkenyl groups having 2 to 20 carbon atoms, such as vinyl, allyl, butenyl, pentenyl, hexenyl, heptenyl, octenyl, nonenyl, decenyl, undecenyl, and dodecenyl; groups containing an acryl group, such as 3-acryloxypropyl and 4-acryloxybutyl; and groups containing a methacryl group, such as 3-methacryloxypropyl and 4-methacryloxybutyl.
[0046] Similarly, the monovalent hydrocarbon group not having a carbon-carbon double bond as R includes: alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, and dodecyl; aryl groups such as phenyl, tolyl, xylyl, naphthyl, anthracenyl, phenanthryl, and pyrenyl; aralkyl groups such as benzyl, phenethyl, naphthylethyl, naphthylpropyl, anthracenylethyl, phenanthrylethyl, and pyrenylethyl; and groups in which the hydrogen atoms of these aryl or aralkyl groups are substituted by alkyl groups such as methyl and ethyl; alkoxy groups such as methoxy and ethoxy; chlorine atoms, bromine atoms, etc.
[0047] In the above average unit formula, X is a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and OX is a hydroxyl group or an alkoxy group having 1 to 3 carbon atoms. Such a hydrolyzable functional group may be a hydroxyl group remaining in the resin during the synthesis of the organopolysiloxane resin, or may be a structure in which the hydroxyl group in the resin is sealed by treatment with a silazane compound or the like during synthesis.
[0048] Here, it is preferred that p is a positive number, q and r are 0 or positive numbers, s is a positive number, t / (p+q+r+s) is a number in the range of 0 to 0.4, (p+q) / (r+s) is preferably in the range of 0.5 to 2.0, and it is particularly preferred that q and r are 0 and the organopolysiloxane resin consists only of M units and Q units.
[0049] The component (B) in the present invention can be selected from
[0050] (B1) an organopolysiloxane resin having a curing reactive group containing a carbon-carbon double bond in the molecule, and
[0051] (B2) an organopolysiloxane resin having no curing reactive group containing a carbon-carbon double bond in the molecule
[0052] The present invention may contain at least one kind of organopolysiloxane resin, but from the viewpoint of improving the curing reactivity and the temperature dependence of the viscoelasticity of the obtained electrode layer, the shape retention of the dielectric layer, etc., it is preferred to contain both the component (B1) and the component (B2). Specifically, the component (B1) and the component (B2) may be used together in a mass ratio of 5:95 to 95:5, preferably in a mass ratio of 5:95 to 50:50.
[0053] Examples include organopolysiloxane resins containing alkenyl groups. The organopolysiloxane resin as component (B1) preferably has the above-mentioned weight average molecular weight, has the above-mentioned M units and Q units, and at least a portion of R is an alkenyl group such as vinyl or hexenyl, and the content of vinyl (CH2=CH-) is in the range of 1.0 to 5.0% by mass, preferably 1.2 to 3.5% by mass. It should be noted that R other than the alkenyl group is not particularly limited, but in industry, other R may be an alkyl group such as methyl and an aryl group such as phenyl. It should be noted that the M unit, the Q unit, and the optionally contained (XO 1 / 2 The preferred ratio and content of the ) units are as described above.
[0054] The organopolysiloxane resin as component (B2) is an organopolysiloxane resin that preferably has the above-mentioned weight average molecular weight, has the above-mentioned M unit and Q unit, and R is a group selected from alkyl groups such as methyl and aryl groups such as phenyl, and does not have a curing reactive group containing a carbon-carbon double bond in the molecule. It should be noted that the M unit, Q unit, and the optionally contained (XO 1 / 2 The preferred ratio and content of the ) units are as described above.
[0055] [Ingredient (C)]
[0056] Component (C) is an optional component of the present composition, and is a cross-linking agent that can react with a curing reactive group containing a carbon-carbon double bond in component (A) or component (B) in the presence of component (D) to form a cured product by hydrosilylation. It should be noted that, in the case where the present composition does not have curing reactivity, for example, only by forming an electrode by drying after hot melting, it is not necessary to use components (C) and components (D). On the other hand, in the case of using the present composition as a cured product after hot melting to form an electrode, it is preferably provided that components (C) and components (D) are included, based on the presence of a curing reactive group containing a carbon-carbon double bond in component (A) or component (B).
[0057] Examples of such component (C) include 1,1,3,3-tetramethyldisiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane, tris(dimethylhydrogensiloxy)methylsilane, tris(dimethylhydrogensiloxy)phenylsilane, methylhydrogenpolysiloxane terminated at both ends of the molecular chain by trimethylsiloxy, dimethylsiloxane / methylhydrogensiloxane copolymer terminated at both ends of the molecular chain by trimethylsiloxy, dimethylpolysiloxane terminated at both ends of the molecular chain by dimethylhydrogensiloxy, dimethylsiloxane / methylhydrogensiloxane copolymer terminated at both ends of the molecular chain by dimethylhydrogensiloxy, methylhydrogensiloxane / diphenylsiloxane copolymer terminated at both ends of the molecular chain by trimethylsiloxy, methylhydrogensiloxane / diphenylsiloxane / dimethylsiloxane copolymer terminated at both ends of the molecular chain by trimethylsiloxy, hydrolysis condensation product of trimethoxysilane, (CH 3 ) 2 HSiO 1 / 2 Unit and SiO 4 / 2 The copolymer composed of (CH 3 ) 2 HSiO 1 / 2 Unit, SiO 4 / 2 Unit and (C 6 H 5 )SiO 3 / 2 The invention also includes copolymers composed of these units and mixtures of two or more thereof.
[0058] The amount of component (C) used is preferably an amount in the range of 0.0 to 10 mol of silicon-bonded hydrogen atoms per 1 mol of carbon-carbon double bonds in the composition, preferably an amount in the range of 0.0 to 5.0 mol, and particularly preferably an amount in the range of 0.0 to 1.5 mol, 0.0 to 0.10. It should be noted that, in the case of a composition in which at least a portion of component (A) is component (A1), at least a portion of component (B) is component (B1), and an electrode is formed by curing, the amount of component (C) used may be an amount in the range of 0.1 to 5.0 mol, 0.1 to 1.5 mol, or 0.1 to 1.00 mol of silicon-bonded hydrogen atoms per 1 mol of carbon-carbon double bonds in the composition. In particular, when the amount of component (C) used is below the above upper limit, the mechanical strength and temperature dependence of the cured product can be easily designed within a practically appropriate range, and there is an advantage that an electrode having a better followability of the electrode layer to the dielectric layer and a better shape retention can be easily obtained.
[0059] [Ingredient (D)]
[0060] Component (D) is an optional structure like component (C), and is a curing reactive group containing a carbon-carbon double bond in the present composition and a catalyst for promoting the hydrosilylation reaction of component (C), and examples thereof include platinum-based catalysts, rhodium-based catalysts, palladium-based catalysts, nickel-based catalysts, iridium-based catalysts, ruthenium-based catalysts, and iron-based catalysts, preferably platinum-based catalysts. As the platinum-based catalyst, examples thereof include platinum-based compounds such as platinum fine powder, platinum black, platinum-supported silica fine powder, platinum-supported activated carbon, chloroplatinic acid, an alcohol solution of chloroplatinic acid, an olefin complex of platinum, and an alkenylsiloxane complex of platinum, and an alkenylsiloxane complex of platinum is particularly preferred. Examples of the alkenylsiloxane include 1,3-divinyl-1,1,3,3-tetramethyldisiloxane, 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane, alkenylsiloxanes in which a part of the methyl groups of these alkenylsiloxanes are substituted with ethyl groups, phenyl groups, etc., and alkenylsiloxanes in which the vinyl groups of these alkenylsiloxanes are substituted with allyl groups, hexenyl groups, etc. In particular, 1,3-divinyl-1,1,3,3-tetramethyldisiloxane is preferred from the viewpoint of good stability of the platinum-alkenylsiloxane complex. Furthermore, from the viewpoint of improving the stability of the platinum-alkenylsiloxane complex, it is preferred to add alkenylsiloxanes such as 1,3-divinyl-1,1,3,3-tetramethyldisiloxane, 1,3-diallyl-1,1,3,3-tetramethyldisiloxane, 1,3-divinyl-1,3-dimethyl-1,3-diphenyldisiloxane, 1,3-divinyl-1,1,3,3-tetraphenyldisiloxane, and 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane, and organosiloxane oligomers such as dimethylsiloxane oligomers to the complex, and it is particularly preferred to add alkenylsiloxanes. In addition, from the perspective of improving workability and the pot life of the composition, these hydrosilylation reaction catalysts may also be thermoplastic resin particles containing hydrosilylation reaction catalysts as catalysts dispersed or encapsulated in thermoplastic resins such as silicone resins, polycarbonate resins, and acrylic resins, and in particular thermoplastic resin particles containing hydrosilylation reaction catalysts containing platinum. It should be noted that as a catalyst that promotes the hydrosilylation reaction, non-platinum metal catalysts such as iron, ruthenium, and iron / cobalt can be used.
[0061] In particular, in the case where the composition involved in the present invention is a composition for forming an electrode by curing, from the viewpoint of improving the stability, workability and pot life of the hot melt composition during production, at least a part of the (D) component preferably includes (D1) thermoplastic resin microparticles containing a platinum hydrosilylation reaction catalyst, and may also be microparticles in which a platinum-based hydrosilylation reaction catalyst is dissolved or dispersed in a thermoplastic resin, or microcapsule microparticles having a structure in which a platinum-based catalyst is contained as a core in a shell of a thermoplastic resin. As a platinum-based catalyst, an alkenylsiloxane complex of platinum similar to that described above can be exemplified. In addition, the thermoplastic resin is not particularly limited as long as it is substantially impermeable to the platinum-based catalyst and substantially insoluble in the organopolysiloxane of the main component of the present composition at least during production and storage of the present composition, but the softening point or glass transition point of the thermoplastic resin is preferably above 80°C, and more preferably above 120°C. Specifically, silicone resins, polysilane resins, epoxy resins, acrylic resins, and methylcellulose polycarbonate resins can be preferably used. The softening point is the temperature at which the resin begins to flow due to its own weight or its own surface tension, and can be measured by observing the crushed particles under a microscope while raising the temperature at a certain speed. In addition, the glass transition point can be measured by DSC (Differential Scanning Calorimeter). In the present invention, it is preferred that either the softening point or the glass transition point is above 120°C. This is because if the softening point or the glass transition point of the thermoplastic resin is lower than 120°C, the platinum component may begin to dissolve in the process of uniformly mixing the present composition described later. In addition, the average particle size of the thermoplastic microparticles containing the platinum catalyst is not limited, but is preferably in the range of 0.1 to 500 μm, and more preferably in the range of 0.3 to 100 μm. This is because it is difficult to prepare thermoplastic resin microparticles containing a platinum catalyst having an average particle size less than the lower limit of the above range, and on the other hand, if the upper limit of the above range is exceeded, the dispersibility in the present composition is reduced.
[0062] The method for preparing such thermoplastic resin microparticles containing a hydrosilylation reaction catalyst containing platinum is not limited, and examples thereof include: chemical methods such as the conventionally known interfacial polymerization method and in-situ polymerization method; physical / mechanical methods such as the coagulation method and the in-liquid drying method. In particular, from the viewpoint of being easier to obtain microcapsule microparticles with a narrow particle size distribution, it is preferred to use the in-liquid drying method and the gas phase drying method using a spray dryer or the like. The microparticles obtained by these methods can be used directly, but in order to obtain a composition with excellent storage stability, it is preferred to wash the microparticles with an appropriate cleaning solvent to remove the platinum catalyst attached to the surface. Here, an appropriate cleaning solvent refers to a cleaning solvent having the property of not dissolving the thermoplastic resin but dissolving the platinum catalyst. As such a cleaning solvent, for example, alcohols such as methanol and ethanol; low molecular weight organopolysiloxanes such as hexamethyldisiloxane, etc. can be cited. The ratio of the catalyst for hydrosilylation reaction to the thermoplastic resin varies greatly depending on the method for producing the granular material, and therefore cannot be particularly limited, but the content of the platinum-based catalyst relative to the thermoplastic resin is preferably 0.01% by mass or more. This is because, when the content of the platinum-based catalyst is less than 0.01% by mass, if the thermoplastic resin particles containing the platinum-based catalyst that are contained in the present composition are not contained in large quantities, the physical properties of the cured product are impaired by the present composition.
[0063] The amount of the hydrosilylation reaction catalyst as component (D) added is a catalytic amount, preferably 0.01 to 500 ppm, 0.01 to 100 ppm, or 0.01 to 50 ppm in terms of metal atoms by mass relative to the entire composition.
[0064] A part or all of the component (D) does not show activity without irradiation with high energy rays, but may be a catalyst for hydrosilylation reaction that shows activity in the composition by irradiation with high energy rays, a so-called high energy ray activated catalyst or a photoactivated catalyst. By using such a component (D), the composition as a whole can achieve the following characteristics: it can be cured even at low temperatures by irradiation with high energy rays as a trigger, has excellent storage stability, and is easy to control the reaction, so it is excellent in workability.
[0065] Examples of high-energy rays include ultraviolet rays, gamma rays, X-rays, alpha rays, electron beams, and the like. In particular, ultraviolet rays, X-rays, and electron beams irradiated by commercially available electron beam irradiation devices are included. Ultraviolet rays are preferred from the perspective of catalyst activation efficiency, and ultraviolet rays with a wavelength of 280 to 380 nm are preferred from the perspective of industrial utilization. In addition, the irradiation amount varies depending on the type of high-energy ray-activated catalyst. In the case of ultraviolet rays, the cumulative irradiation amount at a wavelength of 365 nm is preferably 100 mJ / cm2 ~100J / cm 2 within the range.
[0066] Specific examples of component (D) include (methylcyclopentadienyl)trimethylplatinum (IV), (cyclopentadienyl)trimethylplatinum (IV), (1,2,3,4,5-pentamethylcyclopentadienyl)trimethylplatinum (IV), (cyclopentadienyl)dimethylethylplatinum (IV), (cyclopentadienyl)dimethylacetylplatinum (IV), (trimethylsilylcyclopentadienyl)trimethylplatinum (IV), (methoxycarbonylcyclopentadienyl)trimethylplatinum (IV), (dimethylphenylsilylcyclopentadienyl)trimethylcyclopentadienylplatinum (IV), trimethyl(acetylacetylacetonate)platinum (IV), trimethyl(3,5 -heptanedione) platinum (IV), trimethyl (methyl acetoacetate) platinum (IV), bis (2,4-pentanedione) platinum (II), bis (2,4-hexanedione) platinum (II), bis (2,4-heptanedione) platinum (II), bis (3,5-heptanedione) platinum (II), bis (1-phenyl-1,3-butanedione) platinum (II), bis (1,3-diphenyl-1,3-propanedione) platinum (II), bis (hexafluoroacetylacetonate) platinum (II), among which (methylcyclopentadienyl) trimethyl platinum (IV) and bis (2,4-pentanedione) platinum (II) are preferred from the aspects of versatility and ease of acquisition.
[0067] The amount of the high energy ray activated catalyst used as component (D) is an effective amount and is not particularly limited, as long as it is an amount that promotes the curing of the composition of the present invention. Specifically, the metal atoms in the catalyst are 0.01 to 1,000 ppm by mass relative to the sum of components (A) to (C) (the whole is 100% by mass), and the platinum metal atoms in component (D) are preferably in an amount within the range of 0.1 to 500 ppm.
[0068] [Ingredient (E)]
[0069] Component (E) is conductive fine particles, and there is no particular limitation as long as it is a substance that can provide conductivity to the electrode layer formed using the hot-melt composition involved in the present invention. It should be noted that regarding the electrode layer containing conductive fine particles, for example, in the international patent publication WO2014 / 105959 of the applicant of the present case, etc., it is proposed, but in particular, no content related to the hot-melt composition and carbon nanotubes (CNT) is disclosed.
[0070] Specifically, component (E) includes conductive carbon such as carbon nanotubes (CNT), conductive carbon black, graphite (the present invention also includes graphite coated with a metal such as nickel graphite and other conductive materials), vapor grown carbon (VGCF), etc.; metal powders such as platinum, gold, silver, copper, nickel, tin, zinc, iron, and aluminum; further examples include antimony-doped tin oxide, phosphorus-doped tin oxide, needle-shaped titanium oxide coated with tin oxide / antimony, tin oxide, indium oxide, antimony oxide, zinc antimonate, and pigments coated with tin oxide on the surface of carbon and graphite whiskers; pigments coated with at least one conductive metal oxide selected from the group consisting of tin-doped indium oxide (ITO), fluorine-doped tin oxide (FTO), and phosphorus-doped tin oxide nickel oxide; conductive pigments containing tin oxide and phosphorus on the surface of titanium dioxide particles, etc., and these can also be treated with various surface treatment agents. These can be used alone or in combination of two or more. In order to uniformly disperse these conductive fine particles in the composition, they may be kneaded in advance with a part or all of the components (A) to (C) used in the composition and formulated in the composition in the form of a composite.
[0071] Furthermore, the conductive inorganic particles can also be particles of conductive materials such as metals coated on the surface of fibers such as glass fibers, silica alumina fibers, alumina fibers, carbon fibers, and needle-shaped reinforcing materials such as aluminum borate whiskers and potassium titanate whiskers, and inorganic fillers such as glass beads, talc, mica, graphite, wollastonite, and dolomite.
[0072] In the hot-melt electrode layer forming organopolysiloxane composition involved in the present invention, regardless of whether it is curable or not, at least a part of component (E) preferably contains particles of at least one conductive carbon selected from carbon nanotubes (CNTs), conductive carbon black, graphite and vapor grown carbon (VGCF). These conductive particles have the following advantages: excellent uniform dispersibility in the organopolysiloxane composition, excellent temperature dependence of the viscoelasticity of the electrode layer obtained using the hot-melt composition, and can effectively improve the followability and shape retention of the electrode layer to the dielectric layer.
[0073] In the hot-melt electrode layer-forming organopolysiloxane composition of the present invention, at least a part or all of component (E) is preferably carbon nanotubes (CNTs). CNTs may be single-layer, double-layer, or multi-layer, and their particle size is not particularly limited, but conductive particles containing (E1) single-walled carbon nanotubes (SWCNTs) are particularly preferred.
[0074] Single-walled carbon nanotubes (SWCNTs) are a special type of carbon material known as a one-dimensional material. Single-walled carbon nanotubes are composed of graphene sheets, which are wound into a hollow tube with a wall of one atom thickness. By having such a chemical structure and size, single-walled carbon nanotubes have a tendency to show particularly excellent mechanical, electrical, thermal and optical properties even among other conductive carbons such as acetylene black. In particular, even if used in small amounts, the volume resistivity of the obtained electrode layer can be effectively reduced, and the mechanical strength such as the elongation and tensile strength of the electrode layer at break can be maintained without damaging the temperature dependence of its viscoelasticity. Therefore, in addition to the high performance and high strength of the energy density of the electrode layer, it also has the advantage of being able to particularly effectively improve the followability and shape retention of the electrode layer to the dielectric layer.
[0075] The average outer diameter of the single-walled carbon nanotubes is not particularly limited, but is preferably 2.5 nm or less. It is more preferably 1.0 to 2.5 nm, further preferably 1.1 to 2.0 nm, and particularly preferably 1.2 to 1.8 nm. The average outer diameter of the single-walled carbon nanotubes can be obtained from the light absorption spectrum of the single-walled carbon nanotubes obtained by ultraviolet visible near infrared spectroscopy (UV-Vis-NIR), Raman spectrum, or transmission electron microscope (TEM) image.
[0076] The average fiber length of the single-walled carbon nanotubes is preferably less than 100 μm. It is more preferably 0.1 to 50 μm, further preferably 0.5 to 20 μm, and particularly preferably 1 to 10 μm. The average fiber length of the single-walled carbon nanotubes can be obtained as follows: an AFM image of the single-walled carbon nanotubes is obtained using an atomic force microscope (AFM), or a TEM image of the single-walled carbon nanotubes is obtained using a transmission electron microscope (TEM), the length of each single-walled carbon nanotube is measured, and the total length is divided by the number of single-walled carbon nanotubes measured.
[0077] The G / D ratio of single-walled carbon nanotubes measured by Raman spectroscopy (wavelength 532nm) is preferably 2 or more. It is more preferably 2 to 250, further preferably 5 to 250, particularly preferably 10 to 220, and most preferably 40 to 180. The G / D ratio refers to the intensity ratio (G / D) of the G band and the D band of the Raman spectrum of the single-walled carbon nanotube. The higher the G / D ratio of the single-walled carbon nanotube, the higher the crystallinity of the single-walled carbon nanotube, and the fewer carbon nanotubes with impurity carbon and defects.
[0078] Single-walled carbon nanotubes (SWCNTs) can be obtained as commercial products. For example, in the present invention, TUBALL(TM)MATRIX 601 (polydimethylsiloxane containing 10% by mass of single-walled carbon nanotubes), TUBALL(TM)MATRIX 602 (vinyl ether-terminated polydimethylsiloxane containing 10% by mass of single-walled carbon nanotubes), TUBALL(TM)MATRIX 201 (aliphatic glycidyl ester containing 10% by mass of single-walled carbon nanotubes), TUBALL(TM)MATRIX 202 (aliphatic carboxylic acid ester derivative containing 10% by mass of single-walled carbon nanotubes), TUBALL(TM)MATRIX 204 (methacrylate derivative containing 10% by mass of single-walled carbon nanotubes), TUBALL(TM)MATRIX 301 (ethoxylated alcohol containing 10% by mass of single-walled carbon nanotubes) (all manufactured by Kusumoto Chemicals Co., Ltd.), etc. can be cited.
[0079] Part or all of the above-mentioned conductive particles may be conductive particles whose surfaces are partially or entirely treated by an organosilicon compound. Examples of organosilicon compounds are low molecular weight organosilicon compounds such as silane, silazane, siloxane or the like; and organosilicon polymers or oligomers such as polysiloxane, polycarbosiloxane or the like. Examples of preferred silanes are so-called silane coupling agents. Representative examples of such silane coupling agents are alkyltrialkoxysilanes (methyltrimethoxysilane, vinyltrimethoxysilane, hexyltrimethoxysilane, octyltrimethoxysilane or the like), trialkoxysilanes containing organic functional groups (glycidoxypropyltrimethoxysilane, epoxycyclohexylethyltrimethoxysilane, methacryloxypropyltrimethoxysilane, aminopropyltrimethoxysilane or the like). Preferred siloxanes and polysiloxanes include: hexamethyldisiloxane, 1,3-dihexyltetramethyldisiloxane, trialkoxysilyl single-terminated polydimethylsiloxane, trialkoxysilyl single-terminated dimethylvinyl single-terminated polydimethylsiloxane, trialkoxysilyl single-terminated organic functional group single-terminated polydimethylsiloxane, trialkoxysilyl doubly terminated polydimethylsiloxane, organic functional group doubly terminated polydimethylsiloxane or the like. When using siloxane, the number n of siloxane bonds is preferably in the range of 2 to 150. In addition, siloxane is not necessarily a main chain, but may be a substance obtained by siloxane modification of an organic polymer. As an example, silicone-modified acrylic polymers can be cited. Preferred examples of silazanes are hexamethyldisilazane, 1,3-dihexyltetramethyldisilazane or the like. Preferred polycarbosiloxanes are exemplified by polymers having Si-CC-Si bonds in the polymer backbone.
[0080] The amount of component (E) can be appropriately designed according to the conductivity (i.e., volume resistivity), mechanical strength, and shape retention of the obtained electrode layer. However, in practice, the volume fraction of the conductive fine particles (E) relative to the entire composition is preferably in the range of 0.005 to 0.50, and more preferably in the range of 0.005 to 0.25. Within the range of the amount of component (E), the volume resistivity of the electrode layer obtained using the present composition is 10 2 Ω·cm or less, preferably 10 to 10 2 In the range of Ω·cm, there is an advantage that an electrode layer showing excellent conductivity can be designed, especially when a part of component (E) is fine particles containing conductive carbon, especially when a part of component (E) is single-walled carbon nanotubes (SWCNT), there are the following advantages: the volume resistivity of the electrode layer is effectively reduced to achieve excellent conductivity, and the mechanical strength such as elongation and tensile strength of the electrode layer at break is not impaired, and its viscoelasticity can achieve excellent temperature dependence. In particular, the volume fraction of the single-walled carbon nanotube (SWCNT) relative to the entire composition is preferably in the range of 0.005 to 0.25.
[0081] In the present composition, as long as the purpose of the present invention is not impaired, other optional components may also include (F) reinforcing filler, (G) curing retarder, (H) tackifier and (I) organic wax. It should be noted that, as described later, the present composition may also contain an organic solvent, but is preferably a substantially solvent-free hot melt composition.
[0082] [Ingredients (F)]
[0083] Component (F) is a reinforcing filler, which can sometimes improve the mechanical strength of the electrode layer obtained using this composition. Specifically, it is preferably an average primary particle size of less than one or more reinforcing inorganic particles of 50nm, which can be exemplified by: fumed silica, wet silica, crushed silica, calcium carbonate, diatomaceous earth, finely crushed quartz, various metal oxide powders other than aluminum oxide / zinc oxide, glass fiber, carbon fiber, etc., and these are treated with one or more organosilicon compounds described later. The shape is not particularly limited, and the reinforcing inorganic particles of optional shapes such as particle-shaped, plate-shaped, needle-shaped, and fibrous can be used.
[0084] Preferred examples of component (F) include hydrophilic or hydrophobic fumed silica or metal oxide composites thereof having an average primary particle size of 10 nm or less and capable of partial aggregation. Furthermore, from the perspective of improving dispersibility, it is preferred to use the above-mentioned organosilicon compound.
[0085] The fumed silica or its metal oxide composite is treated. These reinforcing inorganic particles may be used in combination of two or more.
[0086] The BET specific surface area of component (F) can be appropriately selected, but may be 10 m 2 / g or more, and can also be 10 to 1000 m 2 / g. Furthermore, as component (F), two or more reinforcing fillers with different BET specific surface areas may be used together. For example, as component (F), (F1) having an average BET specific surface area of more than 100 m2 and surface treated with one or more organic silicon compounds may be used alone. 2 / g reinforcing fine particles or a composite thereof and (F2) surface-treated with one or more organic silicon compounds and having an average BET specific surface area of 10 to 100 m 2 The reinforcing fine particles or the composite thereof in the range of 100 wt % to 200 wt % can be used together with the component (F1) and the component (F2) at an optional ratio by mass.
[0087] Preferably, component (F) is surface treated with the above-mentioned organosilicon compound, and as preferred organosilicon compounds, one or more selected from hexamethyldisilazane and 1,3-bis(3,3,3-trifluoropropyl)-1,1,3,3-tetramethyldisilazane can be exemplified. It should be noted that, within the scope of not hindering the technical effect of the present invention, surface treatment with a surface treatment agent other than the organosilicon compound can also be used together.
[0088] In the above-mentioned surface treatment, the ratio of the surface treatment agent to the total amount of the filler is preferably in the range of 0.1 mass % to 50 mass %, more preferably in the range of 0.3 mass % to 40 mass %. It should be noted that the treatment amount is the charge ratio of the filler to the surface treatment agent, and the remaining treatment agent is preferably removed after the treatment. In addition, when the treatment is performed as needed, there is no problem in using additives that promote or assist the reaction.
[0089] [Ingredient (G)]
[0090] Component (G) is a curing retarder, and in particular, when the present composition is cured by a hydrosilylation reaction, it can effectively suppress side reactions and further improve the storage stability of the composition of the present invention and the usable time during heating and melting.
[0091] The curing retarder that can be used is not particularly limited in structure and type, and can be selected from known hydrosilylation reaction inhibitors, such as 2-methyl-3-butyn-2-ol, 3,5-dimethyl-1-hexyn-3-ol, 2-phenyl-3-butyn-2-ol, 1-ethynyl-1-cyclohexanol and other alkynols; 3-methyl-3-pentene-1-yne, 3,5-dimethyl-3-hexene-1-yne and other alkynyl compounds; tetramethyltetravinylcyclotetrasiloxane, tetramethyltetrahexenylcyclotetrasiloxane and other low molecular weight siloxanes containing alkenyl groups; methyl-tris(1,1-dimethyl-2-propynyloxy)silane, vinyl-tris(1,1-dimethylpropynyloxy)silane and other alkynyloxysilanes. It should be noted that when the composition is manufactured by a process accompanied by heating such as melt kneading, as component (G), a compound having a boiling point of 200°C or more at atmospheric pressure can also be used.
[0092] As component (G), it is particularly preferred to use a compound having a boiling point of 200°C or more at atmospheric pressure. This is because, from the perspective of uniform composition, if a compound having a low boiling point is used as a curing retarder, part or all of the curing retarder may volatilize during the process of melt kneading, thereby failing to obtain the desired curing delay effect for the final curable silicone composition. It should be noted that methyl-tris(1,1-dimethyl-2-propynyloxy)silane has a boiling point of about 293°C at atmospheric pressure, which can be cited as an example of a preferred component (G).
[0093] The amount of component (G) used is optional, but is preferably within a range of 1 to 10000 ppm by mass based on the entire composition.
[0094] [Ingredient (H)]
[0095] Component (H) is a tackifier, and examples thereof include an organic silicon compound having at least one alkoxy group bonded to a silicon atom in one molecule. Examples of the alkoxy group include: methoxy, ethoxy, propoxy, butoxy, and methoxyethoxy, and methoxy is particularly preferred. In addition, as groups bonded to silicon atoms other than alkoxy groups in the organic silicon compound, examples thereof include: halogen-substituted or non-substituted monovalent hydrocarbon groups such as alkyl, alkenyl, aryl, aralkyl, and halogenated alkyl groups; glycidoxyalkyl groups such as 3-glycidoxypropyl and 4-glycidoxybutyl; epoxycyclohexylalkyl groups such as 2-(3,4-epoxycyclohexyl)ethyl and 3-(3,4-epoxycyclohexyl)propyl; epoxyalkyl groups such as 3,4-epoxybutyl and 7,8-epoxyoctyl; monovalent organic groups containing an acryl group such as 3-methacryloxypropyl; and hydrogen atoms. The organosilicon compound preferably has a group that can react with an alkenyl group or a silicon-bonded hydrogen atom in the present composition, and specifically, preferably has a silicon-bonded hydrogen atom or an alkenyl group. In addition, it can provide good adhesion to various substrates, so the organosilicon compound preferably has at least one monovalent organic group containing an epoxy group in one molecule. As such an organosilicon compound, examples include: an organosilane compound, an organosiloxane oligomer, and an alkyl silicate. As the molecular structure of the organosiloxane oligomer or the alkyl silicate, examples include a linear, a linear having a part of a branched chain, a branched, a cyclic, and a reticular shape, and particularly preferably a linear, a branched, and a reticular shape. Examples of the organosilicon compound include silane compounds such as 3-glycidoxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 3-methacryloxypropyltrimethoxysilane; siloxane compounds each having at least one silicon-bonded alkenyl group or silicon-bonded hydrogen atom and silicon-bonded alkoxy group in one molecule; a silane compound having at least one silicon-bonded alkoxy group or a mixture of a siloxane compound and a siloxane compound each having at least one silicon-bonded hydroxyl group and silicon-bonded alkenyl group in one molecule; a reaction mixture of an amino-containing organoalkoxysilane and an epoxy-containing organoalkoxysilane; an organic compound having at least two alkoxysilyl groups in one molecule and containing bonds other than silicon-oxygen bonds between these silyl groups; an organic compound having the general formula: R a n Si(OR b ) 4-n
[0096] (Where R a is a monovalent organic group containing an epoxy group, R b is an alkyl group having 1 to 6 carbon atoms or a hydrogen atom. n is a number in the range of 1 to 3)
[0097] The epoxy-containing silane or its partial hydrolysis condensate shown, the reaction mixture of the vinyl-containing siloxane oligomer (containing the siloxane oligomer of chain or cyclic structure) and the epoxy-containing trialkoxysilane, methyl polysilicate, ethyl polysilicate and ethyl polysilicate containing epoxy group. The tackifier is preferably a low-viscosity liquid, and its viscosity is not limited, but preferably in the range of 1 to 500 mPa·s at 25°C. In addition, the content of the tackifier is not limited, but preferably in the range of 0.01 to 10 parts by mass relative to a total of 100 parts by mass of the present composition.
[0098] In the present invention, as a particularly preferred tackifier, a reaction mixture of an amino-containing organoalkoxysilane and an epoxy-containing organoalkoxysilane can be exemplified. Such a component is a component that improves the initial adhesion to various substrates, especially the low-temperature adhesion to unwashed adherends, during the formation of the electrode layer obtained using the present composition (after heating and melting and during curing). Such a reaction mixture is disclosed in Japanese Patent Publication No. 52-8854 and Japanese Patent Publication No. 10-195085.
[0099] Examples of alkoxysilanes having an amino group-containing organic group constituting such a component include aminomethyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)aminomethyltributoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, and 3-anilinopropyltriethoxysilane.
[0100] Examples of the epoxy group-containing organoalkoxysilane include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane.
[0101] The ratio of the alkoxysilane having an organic group containing an amino group to the alkoxysilane having an organic group containing an epoxy group is preferably in the range of (1:1.5) to (1:5), and particularly preferably in the range of (1:2) to (1:4) in terms of molar ratio. This component can be easily synthesized by mixing the alkoxysilane having an organic group containing an amino group and the alkoxysilane having an organic group containing an epoxy group as described above and reacting them at room temperature or under heating.
[0102] In particular, the composition of the present invention preferably contains an alkoxysilane having an amino group-containing organic group and an alkoxysilane having an epoxy group-containing organic group, which are cyclized by an alcohol exchange reaction when an alkoxysilane having an amino group-containing organic group is reacted with an alkoxysilane having an epoxy group-containing organic group by the method described in Japanese Patent Application Laid-Open No. 10-195085, and particularly preferably contains a silane having the general formula:
[0103] [Chemical formula 1]
[0104]
[0105] {In the formula, R 1 is an alkyl group, an alkenyl group or an alkoxy group, R 2 are the same or different and are selected from the general formula:
[0106] [Chemical formula 2]
[0107]
[0108] (Where R 4 is alkylene or alkyleneoxyalkylene, R 5 is a monovalent hydrocarbon group, R 6 is an alkyl group, R 7 is an alkylene group, R 8 is an alkyl, alkenyl or acyl group, and a is 0, 1 or 2. )
[0109] The group consisting of the groups shown in the figure, R 3 are the same or different hydrogen atoms or alkyl groups.
[0110] Examples of such a silazolyl derivative include a silazolyl derivative having a silicon atom-bonded alkoxy group or a silicon atom-bonded alkenyl group in one molecule and represented by the following structure.
[0111] [Chemical formula 3]
[0112]
[0113] (In the formula, Rc is a group selected from methoxy, ethoxy, vinyl, allyl and hexenyl.)
[0114] In the present invention, a silazoline derivative represented by the following structural formula may also be used as a thickener.
[0115] [Chemical formula 4]
[0116]
[0117] R in the formula 1 are the same or different hydrogen atoms or alkyl groups, in particular, as R 1, preferably a hydrogen atom or a methyl group. 2 is selected from the group consisting of a hydrogen atom, an alkyl group, and a group of the general formula: -R 4 -Si(OR 5 ) x R 6 (3-x) The same or different groups in the group consisting of the organic groups containing alkoxysilyl groups shown in the figure, wherein R 2 At least one of R is an organic group containing an alkoxysilyl group. 2 The alkyl group of R includes, for example, a methyl group. 2 In the organic group containing an alkoxysilyl group, R 4 is a divalent organic group, and examples thereof include alkylene or alkyleneoxyalkylene, and particularly preferably ethylene, propylene, butylene, methyleneoxypropylene, and methyleneoxypentylene. 5 is an alkyl group having 1 to 10 carbon atoms, preferably a methyl group or an ethyl group. 6 is a substituted or unsubstituted monovalent hydrocarbon group, preferably a methyl group. In the formula, x is 1, 2 or 3, preferably 3.
[0118] As such R 2 Examples of the alkoxysilyl-containing organic group include the following groups.
[0119] -(CH 2 ) 2 Si(OCH 3 ) 2 (CH 2 ) 2 Si(OCH 3 ) 2 CH 3
[0120] -(CH 2 ) 3 Si(OC 2 H 5 ) 2 (CH 2 ) 3 Si(OC 2 H 5 )(CH 3 ) 2
[0121] -CH 2 O(CH 2 ) 3 Si(OCH 3 ) 3
[0122] -CH 2 O(CH 2 ) 3 Si(OC 2 H 5 ) 3
[0123] -CH 2 O(CH 2 ) 3 Si(OCH 3 ) 2 CH 3
[0124] -CH 2 O(CH 2 ) 3 Si(OC 2 H 5 ) 2 CH 3
[0125] -CH 2 OCH 2 Si(OCH 3 ) 2 CH 2 OCH 2 Si(OCH 3 )(CH 3 ) 2
[0126] R in the above formula 3 is at least one group selected from the group consisting of a substituted or unsubstituted monovalent hydrocarbon group, an alkoxy group having 1 to 10 carbon atoms, a glycidyloxyalkyl group, an ethylene oxide alkyl group, and an acyloxyalkyl group, and R 3 As a monovalent hydrocarbon group, an alkyl group such as a methyl group can be exemplified. 3 The alkoxy group of R includes methoxy, ethoxy, and propoxy. 3 The glycidyloxyalkyl group of R is exemplified by 3-glycidyloxypropyl. 3 The oxiranyl alkyl group of R includes 4-oxiranylbutyl and 8-oxiranyloctyl. 3 Examples of the acyloxyalkyl group include acetoxypropyl and 3-methacryloyloxypropyl. 3 , preferably an alkyl group, an alkenyl group, or an alkoxy group, more preferably an alkyl group or an alkenyl group, and particularly preferably a group selected from a methyl group, a vinyl group, an allyl group, and a hexenyl group.
[0127] The amount of component (H) used is not particularly limited, but is preferably in the range of 0.1 to 1.0 mass %, more preferably 0.2 to 1.0 mass %, based on the entire composition, from the viewpoint of improving adhesion to dielectric layers and the like.
[0128] [Ingredients (I)]
[0129] Component (I) is an organic wax, specifically, an organic wax having a melting point in the range of 30 to 160°C. Such component (I) can be exemplified by one or more selected from various hot-melt synthetic resins, waxes, fatty acid metal salts, etc. The wax component exhibits a low kinematic viscosity at high temperature (150°C) to form a melt with excellent fluidity. In addition, by using the above-mentioned (A), (B), and (E) together, the wax component in the melt composed of the present composition rapidly diffuses into the entire composition at high temperature, thereby exhibiting the following effects: reducing the viscosity of the substrate surface to which the molten composition is applied and the entire composition, and sharply reducing the surface friction between the substrate and the molten composition, so that the fluidity of the entire composition is greatly increased. Therefore, sometimes only a very small amount is added relative to the total amount of other components, and the viscosity and fluidity of the molten composition can be greatly improved.
[0130] As long as component (I) satisfies the above-mentioned conditions of the dropping point and the kinematic viscosity when melted, it can also be a petroleum wax such as paraffin, a natural wax such as carnauba wax, a synthetic wax such as montan ester wax, but from the viewpoint of the technical effect of the present invention, it is preferably a hot-melt component composed of a fatty acid metal salt or a fatty acid ester of an erythritol derivative, and is particularly preferably a metal salt of a higher fatty acid such as stearic acid, palmitic acid, oleic acid, isononanoic acid, or pentaerythritol tetrastearate, dipentaerythritol adipic acid stearate, glycerol tri-18-hydroxystearate, pentaerythritol full stearate. Here, the type of the above-mentioned fatty acid metal salt is not particularly limited, and can preferably be exemplified as follows: alkali metal salts such as lithium, sodium, potassium; alkaline earth metal salts such as magnesium, calcium, barium; or zinc salts.
[0131] The amount of component (I) used is 0.01 to 5.0 parts by mass, or 0.01 to 3.5 parts by mass or 0.01 to 3.0 parts by mass, based on 100 parts by mass of the entire composition. If the amount of the wax component used exceeds the upper limit, the adhesion and mechanical strength of the electrode layer obtained by the composition of the present invention may become insufficient. In addition, if the amount used is less than the lower limit, sufficient fluidity during heating and melting may not be achieved.
[0132] [Use of solvent]
[0133] The hot-melt electrode layer-forming organopolysiloxane composition of the present invention is non-flowable (solid or semi-solid) at 25°C and has heating melting properties, so it is essentially unnecessary to use a solvent and can be designed to be solvent-free. No fluorinated solvents, organic solvents, etc. remain in the film obtained by solidification, and it has the advantages of being able to eliminate the problem of environmental load and the influence of solvents on electronic devices. Among them, for the composition involved in the present invention, it does not prevent the use of organic solvents that are inevitably mixed into its raw material components, etc., and a small amount of organic solvents are considered from the perspective of handling. Specifically, the composition involved in the present invention can be a low-solvent to solvent-free composition containing less than 5 parts by mass, preferably less than 1 part by mass, and more preferably less than the detection limit of an organic solvent relative to the sum of the above-mentioned (A), (B), and (E) components (100 parts by mass), and it is preferred. It should be noted that as examples of solvents, one or more organic solvents selected from (S1) organic polar solvents, (S2) low molecular weight siloxane solvents and (S3) halogen solvents or mixed solvents thereof can be exemplified, and in particular, solvents having a boiling point above 80°C and less than 200°C can be exemplified.
[0134] The hot-melt electrode layer-forming organopolysiloxane composition of the present invention is most preferably a solvent-free composition containing substantially no organic solvent and containing no organic solvent at a content of 1 part by mass or less or below the detection limit.
[0135] Furthermore, in the present composition, as long as the purpose of the present invention is not impaired, other optional ingredients may include heat-resistant agents such as iron oxide (red iron oxide), cerium oxide, dimethylsilanol cerium, fatty acid cerium salts, cerium hydroxide, and zirconium compounds; dyes, other pigments other than white, flame retardants, aluminum hydroxide, magnesium hydroxide, zinc borate, zinc molybdate, and phosphazene, heat removers such as hydrotalcite, bismuth oxide, or yttrium oxide. Ion scavengers / pH adjusters; aluminum hydroxide, magnesium hydroxide, zinc borate, zinc molybdate, phosphazene and other flame retardants; hindered phenol compounds, hindered amine compounds, thioether compounds and other antioxidants; pure iron, silicon steel, iron-cobalt alloy, iron-nickel alloy, iron-chromium alloy, iron - Soft magnetic particles such as aluminum alloy, carbonyl iron, stainless steel or composite materials containing one or more of these; inorganic flame retardants (such as hydrated metal compounds such as aluminum hydroxide), halogen flame retardants, phosphorus flame retardants, organic metal salt flame retardants, silicone oil, silicone rubber, polyisoprene, 1,2-polybutadiene, 1,4-polybutadiene and other polybutadiene; styrene-butadiene rubber, acrylonitrile-butadiene rubber, carboxyl-terminated butadiene acrylonitrile rubber, polychloroprene, poly(oxypropylene), poly(oxytetramethylene) glycol, polyolefin glycol, poly-ε-caprolactone and other thermoplastic elastomers; polysulfide rubber, fluororubber and other stress reducing agents; barium titanate (BaTiO 3 ), SrTiO3 ), lead zirconate titanate (Pb(Zr,Ti)O 3 、Other name: PZT、Alumina (Al 2 O 3 , Alias: Aluminum Oxide), Zirconium Oxide (ZrO 2 , alias: zirconium dioxide), magnesium oxide (MgO, alias: magnesium oxide), silicon dioxide (SiO 2 , Other name: silicon oxide), titanium dioxide (TiO 2 , alias: titanium oxide), aluminum nitride (AlN), silicon nitride (Si 3 N 4 ), silicon carbide (SiC), barium calcium zirconate titanate (alias: BCTZ), polyvinylidene fluoride and other dielectric ceramics; copper chloride, cuprous iodide, copper acetate, cerium stearate and other metal salt stabilizers; hindered amines, hindered phenols, sulfur-containing compounds, acrylates, phosphorus organic compounds and other antioxidants or heat stabilizers; benzophenones, salicylates, benzotriazoles and other ultraviolet absorbers or weathering agents, light stabilizers, etc.
[0136] [Use of the present composition: Formation of electrode layer]
[0137] The form of the present composition is not particularly limited, and through its manufacturing process, any form of block, solid to semi-solid wax, granular, granular, pellet (sheet), and sheet can be adopted. In addition, the block, solid to semi-solid paste, granular, and granular composition can be tableted by a known method and used in the form of a pellet-shaped molded product or a sheet-shaped molded product. Similarly, it can be a sheet-shaped molded product obtained by melt-kneading the raw materials using a single-axis or multi-axis (double-axis, etc.) extruder, and laminating the discharged molten kneaded product between release films with a known release layer such as fluorosilicone, etc., or the molten kneaded product can be directly molded into the shape of pellets / sheets according to the shape of the discharge port. In particular, since the present composition itself is non-flowable to solid, it has the advantages of excellent handling and storage stability.
[0138] The present composition has hot melt properties, flows rapidly when heated and melted, can be evenly applied to the desired part, and can form an electrode layer through cooling and an optional curing process, so it can be used without restriction in a solvent-free process and an electrode printing process for the purpose of reducing environmental load and improving the performance of actuators, etc. Further, the present composition has excellent formability, gap filling properties and adhesion when heated and melted, and in addition to the heat resistance, durability and adhesion of the obtained electrode layer, the temperature dependence of the viscoelastic properties is also excellent, so especially in the case of forming an electrode layer formed by using the present composition on a dielectric elastomer sheet, its tracking and shape retention are significantly excellent, even in the case of using a transducer that is based on a high degree of physical displacement as an actuator, it is not easy to cause the problem of peeling and defects of the electrode layer, and it has sufficient viscoelastic properties for practical use.
[0139] The present composition can be used by heating and melting and applying it to the part where the electrode layer is to be formed. Specifically, it can be applied to the part where the electrode layer is to be formed by heat distribution, etc. after a process of heating to 80°C or more and melting, or a sheet-shaped molded object can be arranged at the part where the electrode layer is to be formed and heated to 80°C or more, and the liquefied composition can be applied to the part. It should be noted that the heating and melting temperature is not particularly limited as long as sufficient fluidity, coating and gap filling properties can be achieved, and it can be in the range of 80 to 150°C. In the case of curing reactivity, it is particularly preferred to select the heating and melting temperature according to the type of component (D). For example, as component (D), if it is a thermoplastic resin microparticle containing a platinum hydrosilylation reaction catalyst using a thermoplastic resin with a softening point or glass transition point of 120°C, the hydrosilylation reaction activity is suppressed in the range of 80°C to 120°C. Therefore, if it is within this temperature range, the advantage is that the present composition can be applied to the part where the electrode layer is to be formed by heating and melting without any unexpected curing reaction.
[0140] After the composition is applied to the part where the electrode layer is to be formed, the electrode layer can be formed by curing or curing reaction accompanied by cooling, depending on the presence or absence of curability. It should be noted that the curing reaction can also be carried out by heating and melting at the same time, and high-energy ray irradiation, so that the application of the composition and the curing reaction are carried out simultaneously.
[0141] The present composition can be in a substantially solvent-free form regardless of whether or not it has curing reactivity, and can be applied to a portion where an electrode layer is to be formed after being heated and melted (including application by heating and melting after being arranged at a portion where an electrode layer is to be formed in the case of a shaped article such as a sheet), and can be dried and solidified by cooling to form an electrode layer. In particular, the present composition has the advantage that, even in the form of an uncured or non-curing composition, it can be dried and solidified to form an electrode layer having excellent temperature dependence of viscoelastic properties, and can be used as an electrode layer regardless of whether or not a curing reaction occurs, so that a flexible process design including a solvent-free process can be performed.
[0142] When the present composition is designed as a curing reactive composition, it is applied to the portion where the electrode layer is to be formed after heating and melting (including applying by heating and melting after being arranged at the portion where the electrode layer is to be formed in the case of a shaped article such as a sheet), and a curing reaction is carried out at the same time or after the coating to form an electrode layer composed of a cured product. When components (C) and (D) are used, the curing reaction is a hydrosilylation reaction, and depending on the type of component (D), a heat curing reaction, a curing reaction using high-energy ray irradiation, and a combination thereof can be selected.
[0143] The temperature of the heat curing reaction is not particularly limited, but is preferably 50°C or more and 200°C or less, more preferably 60°C or more and 200°C or less, and further preferably 80°C or more and 180°C or less. In addition, the time taken for the curing reaction is usually 1 second or more and 3 hours or less. In general, a cured product can be obtained by keeping it in the range of 90°C to 180°C for 10 seconds to 30 minutes. It should be noted that, as described above, in the case of selecting thermoplastic resin particles containing platinum hydrosilylation reaction catalysts using thermoplastic resins having specific softening points or glass transition points as component (D), the curing reaction does not proceed at a temperature below the softening point or glass transition point of the thermoplastic resin (wall material), and the curing reaction is rapidly carried out by heating at a temperature above it, so it has the advantage of being easy to control the temperature of the curing reaction.
[0144] When at least a part of component (D) is the above-mentioned high-energy ray-activated catalyst, the present composition performs a curing reaction triggered by irradiation with high-energy rays. As active energy rays that can be used for the curing reaction, ultraviolet rays, electron beams, and radiation, etc. can be listed, but ultraviolet rays are preferred in terms of practicality. In the case of using ultraviolet rays for the curing reaction, it is preferred to add a catalyst for the hydrosilylation reaction that has high activity relative to the ultraviolet rays used, such as bis(2,4-pentanedionate) platinum complex and (methylcyclopentadienyl) trimethylplatinum complex. As the ultraviolet light generating source, high-pressure mercury lamps, medium-pressure mercury lamps, Xe-Hg lamps, and deep ultraviolet lamps (Deep UV Lamp) are preferred, and the irradiation amount at this time is preferably 100 to 8,000 mJ / cm 2 .
[0145] The thickness and shape of the electrode layer can be appropriately designed as desired. When having the above-mentioned volume resistance value (conductivity), it can be in the form of a thin film, and the average thickness thereof is preferably in the range of 1 to 100 μm.
[0146] The electrode layer obtained by the curing reaction has excellent temperature dependence of the viscoelastic properties, and since it is a cured product, the mechanical strength of the electrode layer itself, as well as the adhesion and followability to the substrate, tend to be further improved. By using the electrode layer as the cured product, it has the advantage of being particularly excellent in followability and shape retention. In addition, since the curing reaction is easy to control, a flexible process design including a solvent-free process can be performed.
[0147] [Uses of the present composition: laminate and dielectric layer]
[0148] The electrode layer obtained using this composition can be used for desired semiconductor components and electronic components, etc., can be used for electronic components such as semiconductor chips, electronic circuits, semiconductor (including optical semiconductor) devices, etc. without particular restrictions, and can form a laminate having this electrode layer. In particular, the electrode layer obtained using this composition is excellent in temperature dependence of viscoelastic properties in addition to heat resistance, durability, and adhesion, so in particular, in the case of forming an electrode layer using this composition on a dielectric elastomer sheet, its followability and shape retention are significantly excellent, even in the case of a transducer that is premised on a high degree of physical displacement as an actuator, it is also possible to form a laminate that is not prone to the peeling of the electrode layer, the problem of defects. It should be noted that the type of dielectric elastomer sheet is not particularly limited, but from the perspective of its mechanical strength, heat resistance, flexibility, and electrochemical characteristics, it is particularly preferred as a dielectric layer of an organopolysiloxane cured product film.
[0149] Specifically, a laminate having an electrode layer obtained using the present composition is preferably a laminate having a structure in which (L2) an electrode layer composed of the hot-melt electrode layer-forming organopolysiloxane composition is laminated on at least one surface of (L1) an organopolysiloxane cured film as a dielectric layer.
[0150] Cured organopolysiloxanes having a polysiloxane skeleton have excellent transparency, electrical insulation, heat resistance, cold resistance, etc., and can be improved in electrical activity by introducing high dielectric functional groups such as fluoroalkyl groups as desired, and can be easily processed into a film or sheet shape. Therefore, they are particularly suitable for use as dielectric layers as adhesive films for various electrical / electronic equipment and electroactive films for transducer devices such as actuators.
[0151] The curing mechanism of the organopolysiloxane cured film is classified into hydrosilylation reaction curing type, condensation reaction curing type, peroxide curing type, etc. It is rapidly cured by being left at room temperature or heated, and does not produce by-products. Therefore, it is particularly preferred to use an organopolysiloxane cured film of a curable organopolysiloxane composition of the hydrosilylation reaction curing type.
[0152] The organopolysiloxane cured film as the dielectric layer is in the form of a thin film, and the average thickness of the film is preferably in the range of 1 to 200 μm, the average thickness is preferably in the range of 1 to 150 μm, and the average thickness is more preferably in the range of 1 to 100 μm. Here, the average thickness of the film is the average value of the thickness at the center of the film. Preferably, the organopolysiloxane cured film is uniform and flat, and in the width direction of the film, it is more preferred that the difference between the thickness at the end and the thickness at the center is within 5.0%, and the average value of the thickness at the center of the film is in the range of 5 to 200 μm.
[0153] Similarly, when the number of internal defects of the cured organopolysiloxane film as the dielectric layer is measured using an optical cell within a unit area of 15 mm×15 mm at an optional location, the number of internal defects is in the range of 0 to 20, preferably in the range of 0 to 15. If the number of internal defects exceeds the upper limit described above, dielectric breakdown may occur easily when a high voltage is applied to the film, and the dielectric breakdown strength of the entire film may be significantly reduced.
[0154] The dielectric breakdown strength of the cured organopolysiloxane film as the dielectric layer is in the range of 56 V / μm to 200 V / μm, more preferably in the range of 58 V / μm to 100 V / μm, as measured at room temperature.
[0155] The amount of the introduced high dielectric functional group such as fluoroalkyl group and the high dielectric filler can be easily designed so that the relative dielectric constant of the entire film at 1 kHz and 25° C. is 3 or more, 4 or more, 5 or more, or 6 or more.
[0156] When the organopolysiloxane cured film as the dielectric layer is heat-molded into a sheet shape having a thickness of 2.0 mm, it can be designed to have the following mechanical properties measured in accordance with JIS K 6249.
[0157] (1) The Young's modulus (MPa) can be 10 MPa or less at room temperature, and a particularly preferred range is 0.1 to 2.5 MPa.
[0158] (2) The tear strength (N / mm) can be 1 N / mm or more at room temperature, and a particularly preferred range is 2 N / mm or more.
[0159] (3) The tensile strength (MPa) can be 1 MPa or more at room temperature, and a particularly preferred range is 2 MPa or more.
[0160] (4) The elongation (%) at break can be 50% or more, and a particularly preferred range is 100 to 1000%.
[0161] When the cured organopolysiloxane film as a dielectric layer is used as an electronic material such as a touch panel, an electronic component for a display device, and particularly a transducer material such as a sensor, the shear storage modulus at 23° C. is preferably within a range of 10 3 ~10 5 Pa, more preferably 1.0×10 3 ~5.0×10 4 Within the range of Pa.
[0162] As described above, the average thickness of the organopolysiloxane cured film as the dielectric layer is within the range of 1 to 200 μm per sheet, but a plurality of films may be stacked to form a laminated film having a thickness exceeding 200 μm for the purpose of forming a dielectric layer.
[0163] [Formation of Laminated Body]
[0164] The above-mentioned laminated body can be preferably obtained by, for example, a method for producing a laminated body comprising the following steps: step I: a step of curing a curable organopolysiloxane composition that provides a dielectric layer by curing into a film-like shape, thereby obtaining an organopolysiloxane cured product film as a dielectric layer; step II: a step of heating and melting the above-mentioned hot-melt type electrode layer-forming organopolysiloxane composition on the organopolysiloxane cured product film or its precursor involved in step I, and then applying the composition to form an electrode layer, simultaneously with step I or after step I. It should be noted that the application after heating and melting in step II includes, in addition to the step of applying the heated and molten composition to the portion where the electrode layer is to be formed on the dielectric layer or its precursor by heat distribution, the step of placing a sheet-like molded object on the portion where the electrode layer is to be formed on the dielectric layer or its precursor, heating it to 80° C. or above, and applying the liquefied composition to the portion. Furthermore, the formation of the electrode layer includes: the formation of the electrode layer by cooling the heated and molten composition to dry it, and the formation of the electrode layer as a cured product by the curing reaction of the heated and molten composition.
[0165] In particular, when the curing reaction involved in the formation of the dielectric layer involved in the above-mentioned step I and the formation of the electrode layer involved in the step II are curing reactions accompanied by the formation of a cured product, and when these curing reactions both include a hydrosilylation reaction, by selecting a composition in which the ratio of hydrogen atoms bonded to silicon atoms (hereinafter sometimes abbreviated as "SiH / Vi ratio") in the organohydrogenpolysiloxane component is different from each other, relative to 1 mol of the total amount of carbon-carbon double bonds in the curable organopolysiloxane composition involved in the formation of the dielectric layer or the hot-melt electrode layer-forming organopolysiloxane composition, it is sometimes possible to provide a structure in which two layers are chemically bonded by a hydrosilylation reaction at the interface between the dielectric layer and the electrode layer, thereby further improving the followability and shape retention of the electrode layer involved in the present invention to the dielectric layer, and suppressing the peeling and defect generation of the electrode layer.
[0166] As an example, for the hot-melt electrode layer-forming organopolysiloxane composition of the present invention, its SiH / Vi ratio ([SiH / Vi] Elec ) is 0.2 mol or more and 1.5 mol or less, preferably 0.3 mol or more and 1.2 mol or less, and more preferably 0.3 mol or more and 1.0 mol or less. For the curable organopolysiloxane composition for forming the dielectric layer, its SiH / Vi ratio ([SiH / Vi] DEAP ), particularly preferably [SiH / Vi] Elec / [SiH / Vi] DEAPThe value is in the range of 0.20 to 0.90, 0.33 to 0.85, 0.50 to 0.75, and 0.58 to 0.67. That is, it is particularly preferred that the composition forming the dielectric layer is a combination with a certain degree of excess SiH. This is because, in the case where these curable organopolysiloxane compositions are cured by a hydrosilylation reaction, in the interface thereof, the excess SiH groups present on the dielectric layer side are easily hydrosilylated with the curable reactive groups containing carbon-carbon double bonds in the electrode layer forming organopolysiloxane composition at the interface of the two layers, and it is easy to provide a two-layer chemically bonded structure. This manufacturing method is particularly useful as a method for forming an electrode layer in a transducer component, and can easily provide a dielectric layer and an electrode layer firmly bonded in industry, and is not prone to peeling or defects caused by its insufficient bonding strength and tracking properties. Laminated bodies, electronic parts or display devices.
[0167] The laminate of the organopolysiloxane cured film of the present invention is useful as an electronic material, a component for a display device, or a component for a transducer (including a sensor, a speaker, an actuator, and a generator), and can be used as an electroactive film (including a high dielectric film) with an electrode layer, preferably as a component of an electronic component or a display device. Further, as described above, the electroactive film with high dielectric breakdown strength is preferably a transducer component of an actuator, etc. in the form of a single layer or a laminated film, and the electrode layer of the present invention has the following characteristics: it can be formed on the dielectric layer without special restrictions even in a solvent-free process or an electrode printing process accompanied by heating and melting, and the followability and shape retention of the organopolysiloxane cured film as a dielectric layer are significantly excellent, and it is not easy to produce the problem of peeling and defects of the electrode layer, so it is particularly useful for the actuator application started at a high voltage.
[0168] It should be noted that the laminate of the cured organopolysiloxane film of the present invention preferably has a whole or partial structure, wherein the whole or partial structure has an electrode layer on one side of the dielectric layer, these layers are alternately stacked, and the electrode layer is arranged on the outside. Furthermore, the laminate of the present invention may have a pressure-sensitive adhesive layer used for the purpose of being arranged in the transducer, and a non-silicone thermoplastic resin layer that may optionally have a release surface, in addition to the electrode layer of the present invention and the single-layer or multi-layer dielectric layer.
[0169] Example
[0170] The present invention will be described below with reference to Examples, but the present invention is not limited to these Examples. The following compounds were used in the Examples shown below.
[0171] Component (a1-1): a dimethylsiloxane polymer terminated with vinyldimethylsiloxane groups at both ends (vinyl content: 0.09 mass %, siloxane polymerization degree: 835)
[0172] Component (a1-2): a dimethylsiloxane polymer terminated with vinyldimethylsiloxane groups at both ends (vinyl content: 1.53% by mass, degree of siloxane polymerization: 45)
[0173] Component (b-1): trimethylsilyl units (M), vinyldimethylsilyl units ( vi M) and tetrafunctional siloxy units (Q, SiO 4 / 2 ) units (vinyl content: 1.9 mass %, weight average molecular weight in terms of polystyrene measured by GPC (gel permeation chromatography) using tetrahydrofuran as solvent: Mw = 2.4 × 10 4 )
[0174] Component (b-2): trimethylsiloxy units (M) and tetrafunctional siloxane units (Q, SiO 4 / 2 ) units (using toluene as solvent, the weight average molecular weight in terms of polystyrene measured by GPC is Mw=6.4×10 3 )
[0175] Component (b-3): trimethylsiloxy units (M) and tetrafunctional siloxane units (Q, SiO 4 / 2 ) units (using toluene as solvent, the weight average molecular weight in terms of polystyrene measured by GPC is Mw=3.4×10 3 )
[0176] Component (c-1): dimethylsiloxane polymer terminated with dimethylhydrogensiloxy groups at both ends (silicon-bound water content: 0.123 mass %)
[0177] Component (c-2): a dimethylsiloxy-methylhydrosiloxy-siloxane copolymer having both ends blocked with trimethylsiloxy groups (silicon-bound water content: 0.71% by mass).
[0178] Component (d1): Masterbatch containing microparticles containing a platinum catalyst (*)
[0179] (*) A master batch containing fine particles containing a platinum catalyst prepared by the method shown in the following reference example (the platinum metal concentration is 0.16 mass%)
[0180] [Reference Example (Preparation of Masterbatch Containing Thermoplastic Resin Microparticles Containing Platinum Catalyst)]
[0181] Into a flask equipped with a stirrer, 900 g of a bisphenol A-type thermoplastic polycarbonate resin (glass transition temperature (Tg) 145°C; wall material), 500 g of toluene, and 4600 g of dichloromethane were added and uniformly mixed. 44.4 g of a divinyltetramethyldisiloxane solution of a platinum (0-valent) divinyltetramethyldisiloxane complex (platinum metal concentration of 5% by mass) was added and mixed to obtain a uniform solution. The solution was sprayed / dried using a spray dryer with nitrogen as a hot air flow to obtain 450 g of spherical thermoplastic resin particles containing a platinum catalyst (average particle size of 1.1 μm).
[0182] Next, 40 parts by mass of the thermoplastic resin particles containing the platinum catalyst were mixed with 60 parts by mass of dimethylpolysiloxane having a viscosity of 350 mPa·s and a vinyl content of 0.47% and having both ends of the molecular chain capped with dimethylvinylsiloxane groups, to prepare a master batch containing particles containing the platinum catalyst. The concentration of platinum metal in the master batch was 0.16% by mass.
[0183] Component (d2): a dimethylsiloxane polymer solution capped with vinyldimethylsiloxy groups at both ends of a platinum-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex (about 0.6% by mass in terms of platinum concentration)
[0184] <Conductive filler>
[0185] Component (e): single-walled carbon nanotube (SWCNT, 10% by mass of a dimethylsiloxane polymer terminated with trimethylsiloxy groups at both ends, TUBALL(TM)MATRIX 601)
[0186] <Hydrosilylation Reaction Inhibitor>
[0187] Component (f): 1-ethynylcyclohexanol
[0188] [Examples 1 to 4, Comparative Examples 1 to 4]
[0189] The composition of each experimental example is shown in Table 1 (Example) and Table 2 (Comparative Example). The numerical value corresponding to each component is mass %, and the sum is 100 mass %. In addition, in the following examples, except for Example 1, the silicon atom-bonded hydrogen atom (Si-H) of component (c) is used in an amount of 0.35 to 0.46 moles per 1 mole of vinyl (unsaturated hydrocarbon group, the same below) in the composition. Further, the physical properties before or after curing measured by the following method are shown in Table 1 and Table 2.
[0190] [Volume fraction of each component]
[0191] In the present invention, the true density of each component in the composition is defined as follows and the volume fraction is calculated: 1.23 g / cc for component (b), 1.58 g / cc for single-walled carbon nanotubes (SWCNT) in component (e), and 0.98 g / cc for other components.
[0192] [Mw of component (b)]
[0193] When the component (b) is mixed and used, Mw is calculated as follows.
[0194]
[0195] In the above formula (1), Mwk and wfk are the Mw of the kth component (b) and the weight fraction of the kth component (b), respectively.
[0196] [Sample production]
[0197] After weighing ingredients other than component (d) into a 300cc wide-mouth glass sample bottle, heat in an oven at 125°C for about 30 minutes. Then, on a hot plate heated to 180°C, scrape off the attachments on the wall of the sample bottle while mixing with an electric stirrer for more than 30 minutes. After cooling, add component (d) and mix with an electric stirrer on a hot plate heated to 120°C while scraping off the attachments. Then, transfer the mixture to a 100cc HDPE container and heat in an oven at 110°C for more than 10 minutes. Take it out of the oven and mix it at 2000RPM for more than 4 minutes using a Thinky mixer (ARE-310).
[0198] [Viscoelasticity measurement]
[0199] The storage modulus was measured by a viscoelasticity measuring device (manufactured by Anton Paar, model MCR302). On the lower plate of a Peltier element temperature control system heated to 120°C, an appropriate amount of each curable composition was placed, and the sample was placed to a thickness of about 1.5 mm using a parallel plate with a diameter of 15 mm. Under the conditions of a frequency of 1 Hz and a deformation of 0.1%, after cooling to -20°C at 3°C per minute, the temperature was raised to 150°C and maintained for 180 minutes to cure. Among them, Example 1 was not cured. Furthermore, cooling and heating were repeated again. The storage modulus (G') and loss tangent (tanδ) before and after curing at 25°C and 110°C are shown in Tables 1 and 2. It should be noted that if the ratio of the value of G' before curing at 110°C to the value of G' before curing at 25°C is less than 0.5, the processability is excellent.
[0200] [Production of Cured Material]
[0201] A mold of 50 mm in length × 50 mm in width × 2 mm in thickness is placed on a metal plate, and a PTFE film (150 microns thick) is set on it. An appropriate amount of each composition is placed on the PTFE film and heated in an oven at 120°C for more than 30 minutes. Take it out of the oven, set a PTFE film on the composition, and further clamp it with a metal plate. After that, pressurize and cure at 150°C for 15 minutes, and further perform post-cure in an oven at 150°C for 45 minutes to obtain a sheet-like cured product (a sheet-like molded product without a curing reaction in Example 1).
[0202] [Volume resistivity measurement VR]
[0203] A sheet having a thickness of about 2 mm was prepared under the above conditions, and the analysis was performed using LORESTA-GP MCP-T610 (PSP probe, manufactured by Mitsubishi Chemical Analytical Tech Co., Ltd.) at about 25° C. The values calculated using the correction coefficients according to the sample shape are shown in Tables 1 and 2.
[0204] [Table 1]
[0205]
[0206] [Table 2]
[0207]
[0208] [Summarize]
[0209] As described above, in Examples 1 to 4, the temperature dependence of the viscoelasticity of the composition is high before curing, and the ratio of the value of G'110°C to G'25°C before curing is 0.5 or less. Therefore, it is easy to soften by heating, and it can be said that the coating property is excellent. In Example 1, by drying after melting, an electrode layer having the viscoelasticity and its temperature dependence shown in Table 1 can be formed. In addition, in Examples 2 to 4, by heating and curing at a temperature above the glass transition point (Tg) of the wall material of component (d) after heating and melting, an electrode layer (film) as a cured product having moderate viscoelasticity can be obtained. Here, the volume resistivity of each electrode layer sheet in Examples 1 to 4 is kept low at 10 2 Ω·cm or less, and as an electrode layer for various transducer applications represented by actuators, in addition to the above-mentioned viscoelastic properties, it also has excellent performance in terms of conductivity.
[0210] On the other hand, in Comparative Examples 1 to 2, since the weight % of component (b) is less than 45%, the temperature dependence of viscoelasticity is small. In Comparative Example 3, since there is no component (b), the temperature dependence of viscoelasticity is almost invisible. Therefore, heating is not used to improve processability, and even if coating is performed, it is difficult to maintain the shape, etc. In addition, in Comparative Example 4, the Mw of component (b) is small, and even if it is prepared in a manner with a volume fraction of 0.5, the temperature dependence of viscoelasticity is small. Therefore, it is difficult to further reduce the volume fraction of conductive particles, and as an electrode layer forming composition, the freedom of composition improvement is greatly limited.
Claims
1. A hot-melt electrode layer-forming organopolysiloxane composition, the hot-melt electrode layer-forming organopolysiloxane composition comprising: (A) chain organopolysiloxane; (B) an organopolysiloxane resin having a weight average molecular weight of 5000 or more in terms of standard polystyrene, comprising R3SiO 1 / 2 (wherein R independently represents a monovalent organic group) and the siloxane unit (M unit) represented by SiO 4 / 2 The siloxane units (Q units) shown; and (E) conductive particles, The composition is non-fluid at 25° C. and has heat-melting properties, and the content of the component (B) in the composition is 45% by mass or more based on the entire composition.
2. The hot-melt electrode layer-forming curable organopolysiloxane composition according to claim 1, wherein: Before electrode formation, the shear storage modulus (G') of the composition at 100 °C 110℃ ) and shear storage modulus (G') at 25 °C 25℃ ) value ratio (G' 110℃ / G' 25℃ ) is less than 0.
5.
3. The hot-melt electrode layer-forming organopolysiloxane composition according to claim 1, characterized in that: The conductive fine particles are fine particles containing at least one conductive carbon selected from the group consisting of carbon nanotubes (CNTs), conductive carbon black, graphite, and vapor grown carbon (VGCF).
4. The hot-melt electrode layer-forming organopolysiloxane composition according to claim 1, characterized in that: The conductive fine particles are fine particles including single-walled carbon nanotubes (SWCNTs).
5. The hot-melt electrode layer-forming organopolysiloxane composition according to claim 1, wherein: The volume fraction of the conductive fine particles relative to the entire composition is in the range of 0.005 to 0.50, and the volume resistivity of the electrode layer obtained using the present composition is 10 2 Ω·cm or less.
6. The hot-melt electrode layer-forming organopolysiloxane composition according to claim 1, wherein: The invention comprises: (A1) a linear organopolysiloxane having a curing reactive functional group containing a carbon-carbon double bond at least at both ends of the molecular chain; (B) an organopolysiloxane resin having a weight average molecular weight of 5,000 or more in terms of standard polystyrene, comprising R3SiO 1 / 2 (wherein R independently represents a monovalent organic group) and a siloxane unit (M unit) composed of SiO 4 / 2 The siloxane units (Q units) shown; (C) an organohydrogenpolysiloxane composition having at least two silicon-bonded hydrogen atoms in its molecule, wherein the silicon-bonded hydrogen atoms in this component are present in an amount of 0.0 to 1.5 mol per 1 mol of the total amount of carbon-carbon double bonds; (D) an effective amount of a catalyst for a hydrosilylation reaction; and (E1) conductive microparticles comprising single-walled carbon nanotubes (SWCNTs), The volume fraction of the single-walled carbon nanotube (SWCNT) relative to the entire composition is in the range of 0.005 to 0.
25.
7. The hot-melt electrode layer-forming organopolysiloxane composition according to claim 6, wherein: At least a portion of component (C) is (C1) an organohydrogenpolysiloxane having only silicon-bonded hydrogen atoms at both ends of the molecular chain, and the silicon-bonded hydrogen atoms in component (C) are in an amount of 0.1 to 1.00 mol per 1 mol of the total amount of carbon-carbon double bonds in the composition.
8. The hot-melt electrode layer-forming organopolysiloxane composition according to claim 6, wherein: At least a part of the component (D) is thermoplastic resin fine particles containing (D1) a hydrosilylation reaction catalyst containing platinum.
9. A laminate having a structure in which two or more layers of organopolysiloxane cured film having different compositions are laminated, and having A structure in which (L2) an electrode layer composed of the hot-melt electrode layer-forming organopolysiloxane composition according to any one of claims 1 to 8 is laminated on at least one surface of a cured organopolysiloxane film (L1) as a dielectric layer.
10. The laminate according to claim 9, wherein (L1) The organic polysiloxane cured film as the dielectric layer is a cured film formed by curing through a hydrosilylation reaction, and (L2-1) the electrode layer is composed of the hot-melt electrode layer-forming organic polysiloxane composition described in any one of claims 6 to 8, and has a structure in which the organic polysiloxane cured film as the dielectric layer and the electrode layer are chemically bonded at their interface. 11 . A transducer member, comprising the laminate according to claim 9 or 10. 12 . A transducer comprising the laminate according to claim 9 or 10. 13 . An electronic component or a display device, comprising the laminate according to claim 9 or 10.
14. The method for producing a laminate according to claim 9 or 10, wherein: have: Step I: a step of curing a curable organopolysiloxane composition that provides a dielectric layer by curing into a film form, thereby obtaining an organopolysiloxane cured film as a dielectric layer; Step II: A step of forming an electrode layer by heating and melting the hot-melt electrode layer-forming organopolysiloxane composition according to any one of claims 1 to 8 and applying the composition onto the organopolysiloxane cured film or its precursor involved in step I simultaneously with or after step I. 15 . A method for forming an electrode layer in a transducer member, the method for forming an electrode layer in a transducer member comprising the method for producing a laminate according to claim 14 .
Citation Information
Patent Citations
JP1977008854B2
Carbasilatrane derivative, its production, adhesion accelerator and hardenable silicone composition
JP1998195085A
Curable organopolysiloxane composition for transducers and applications of such curable silicone composition for transducers
WO2014105959A1
Multilayer body composed of cured organopolysiloxane films, use of same, and method for producing same
WO2022004462A1